The Effect of Nopal Mucilage Addition on the Corrosion Rate of Reinforcement Steel in Concrete - Enrique Martínez-Barrios; UIises Páramo-García; Edgardo Jonathan Suárez-Domínguez; Josué Francisco Pérez-Sánchez (Surfaces, 2025)
Environmental humidity is a determining factor in the degradation of concrete structures, particularly in the corrosion process of reinforcement bars. This study analyzed four concrete mixtures with different mucilage contents replacing mixing water: 0, 5, 10, and 15%. Two sets of specimens were fabricated and subjected to a 420-day test period under two different working conditions: natural environmental conditions and high-humidity conditions. Open-circuit potential parameters were analyzed to compare the behavior of the mixtures and determine the corrosion rate. It was observed that under environmental conditions, the mixtures with 0% and 15% mucilage exhibited higher corrosion rates, with values of 0.046 and 0.049 mm/year, respectively, compared to the mixtures with low mucilage additions of 5% and 10%, which showed values of 0.041 and 0.038 mm/year, respectively. The corrosion rates of the mixtures under high-humidity conditions were 0.010 for M0, 0.009 for M1 and M2, and 0.014 for M3. The results indicate that mixtures with 5% and 10% mucilage show better corrosion protection, suggesting that this approach could be a sustainable, low-cost solution to enhance the durability of concrete structures, particularly in coastal areas with high humidity levels. It is concluded that adding nopal mucilage in low concentrations as a substitute for mixing water in concrete formulations not only modifies the properties of concrete, but also reduces the corrosion rate of reinforcement steel under high-humidity conditions, thereby extending the service life of constructions.